Controlled-scattering resonances in a spherical potential well - Akala, Andrew; Banjo, C. Yinka (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Understanding of collision processes is required in designing robust nano-particles for future applications. This study proposes a technique for controlling scattering resonances by using the tuning of well parameters to impose pre-determined thresholds on resonances and bound states in collision processes. The theoretical concept of scattering in a spherical potential well, at varying depths was adopted. A scan of q from 0 to 5Ï€ at incremental steps of q= Ï€/p yields (p x 5)+1 number of state(s), and p-1 state(s) resonate(s) at each bound state.